Analisis Strategi Promosi dan Kualitas Pelayanan Terhadap Kepuasan Pengguna Best Car Care Bogor - Rani Rani; Vina Islami; Syahrir Syahrir (Journal of Business and Economics Research (JBE), 2021)
The development of the automotive industry at this time can be quite rapid because every year the number of vehicles continues to increase. The development of the automotive industry also encourages the development of industries supporting services such as car repair shops, car salons, sales of spare parts, the sale of accessories, and car wash services. Own car wash services are needed the car users because, in addition to saving time, the car users are also convinced that if their car is washed at the car wash, the car will be clean and well maintained. In offering their services, employers must implement appropriate promotional strategies. Quality of service also supports the company to provide satisfaction for its customers. The purpose of this study is to determine the effect of promotion strategies and quality of service on user satisfaction at Best Car Care Bogor partially or simultaneously. A population of 220 people and take a sample of 135 respondents. The research method using multiple regression analysis. Results of research conducted found that the promotion strategy and service quality and significant positive effect either simultaneously or partially on user satisfaction. Advice for employers Best Car Care Bogorfor more attention to the satisfaction of the users of services Best Car Care Bogor, to increase the use of services